The Effect of Prenatal Exercise on Lower Back Pain in Third Trimester Pregnant Women at Likupang Community Health Center - Indria Natasya Matei; Anik Purwati (Journal of Educational Innovation and Public Health, 2025)
Significant physical and psychological changes occur throughout pregnancy, especially in the third trimester (weeks 27–40).  Lower back pain, frequently caused by poor posture, changes in the curvature of the spine, and increasing body weight that shifts the center of gravity forward, is a common issue during this time.  Between 30% and 78% of pregnant women report experiencing lower back discomfort.  Maintaining physical health, endurance, and mental preparedness for childbirth are key objectives of prenatal exercise.  This study aimed to examine the effect of pregnancy exercise on lower back discomfort in third-trimester pregnant women at the Likupang Community Health Center.  The study used a one-group pretest-posttest design and was pre-experimental in nature, with the Likupang Community Health Center serving as the research site.  Fifteen pregnant women from the Likupang Community Health Center were chosen as the study sample.  The results indicated that pregnancy exercise had a significant impact on reducing back pain (p-value 0. 000), showing a clear effect between pregnancy exercise and the reduction of lower back pain (p-value 0. 000), as confirmed by the bivariate statistical test.  The findings suggest that pregnancy exercise can effectively alleviate lower back discomfort in third-trimester pregnant women.